ONE OF THE SOLUTIONS TO THE WASTE PROBLEM IN PALANGKA RAYA CITY WITH BRIQUETTES - Danar Ariangga Windra Gautama; Slamet Winaryo (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
Palangka Raya City faces serious challenges related to waste management, especially the abundant organic waste. This study explores the utilization of organic waste into briquettes as an innovative solution to reduce the volume of waste in landfills and create an alternative energy source. Through thermal conversion and compression methods, organic waste is converted into briquettes that have a high calorific value with low emissions. The research results show that each 1 kilogram of briquettes can be produced from 10 kilograms of dry organic waste, providing a sustainable and environmentally friendly solution for Palangka Raya City. This study also compares data related to waste in Palangka Raya with previous research and provides relevant literature as a reference